The Relationship between Nutritional Knowledge and Body Image with Eating Behavior - Rima Melyana Anjelita; Satwika Arya Pratama; Amalia Ruhana; Noor Rohmah Mayasari (Universitas Negeri Semarang, 2024)
Background: Eating behavior can affect the health condition of a person's body. Nutrition knowledge determines a person's behavior when choosing the food to consume. In addition to nutritional knowledge, a person's view of their body image also affects their eating behavior. This study aims to determine the relationship between nutritional knowledge and body image with eating behavior in the Ambassadors of the Faculty of Clothing, State University of Surabaya (Unesa). Methods: This type of research is cross-sectional. The sample in this study is all Unesa Faculty Ambassadors, totaling 95 respondents. Data collection was carried out by providing test sheets and questionnaires to respondents. Test sheets for nutritional knowledge, questionnaire (MBSRQ-AS) Multidimensional Body Self-Relation questionnaire appearance Scales for body image, and questionnaire (AFHC) Adolescent' Food Habit Checklist for eating behavior. The statistical test used is the Chi-square test. Results: The results showed the p-value value in each research variable, namely nutritional knowledge and eating behavior (0.215), while the variables of body image and eating behavior (0.000). Conclusion: The conclusion is that there is no relationship between nutritional knowledge variables and eating behavior; there is a significant relationship between body image variables and eating behavior.